Coronary atherosclerosis progression in patients after coronary stenting, depending on a cardiology follow-up strategy - A. M. Shchinova; A. K. Osokina; A. V. Potekhina; I. I. Shestova; A. Yu. Filatova; Yu. A. Dolgusheva; Yu. E. Efremova; S. I. Provatorov (Российский кардиологический журнал)
Aim. To compare the prevalence of coronary atherosclerosis in patients after coronary stenting (CS) receiving outpatient and remote cardiology follow-up during a one-year study.Material and methods. We enrolled 279 patients aged 61,5±9,5 years with class ≥II stable angina or silent ischemia after CS. Three groups were formed: group 1 (n=96) — outpatient visits before CS, 1, 3, 6 and 12 months after CS. Group 2 (n=95) — remote monitoring: patients were followed up by a primary care physician with the involvement of a cardiologist via remote communication (e-mail, telephone, Skype) 1, 3, 6 and 12 months after CS. Group 3 (n=88) were followed up by a primary care physician and contacted with the study coordinator before and 12 months after CS. After 12 months, all patients underwent stress-induced myocardial ischemia testing. In case of a positive or uncertain test result, coronary angiography (CA) was performed.Results. Stress-induced myocardial ischemia 12 months after CS was verified in 58 patients (21%): 19 patients (19,8%) — group 1; 9 patients (9,5%) — group 2; 30 patients (34,1%) — group 3 (p<0,05). Repeat CA was performed in 96 patients (34,4% of the total number of patients). Restenosis was detected in 8 (2,9%) patients, coronary atherosclerosis progression — in 38 (13,6%), combination of restenosis and atherosclerosis progression — in 4 (1,4%) patients. Coronary atherosclerosis progression was significantly more frequent in group 3: 10,4%, 9,5% and 21,6% in groups 1, 2 and 3, respectively (p<0,05). The incidence of stent restenosis was comparable: 2,1%, 3,2% and 3,5% in groups 1, 2, and 3, respectively.Conclusion. Coronary atherosclerosis progression was the main reason for repeated revascularizations 12 months after the CS. Outpatient and remote cardiology follow-up is associated with a lower incidence of coronary atherosclerosis progression and repeated CA during 12-month follow-up after CS.